2022
DOI: 10.3390/jof8020212
|View full text |Cite
|
Sign up to set email alerts
|

Conventional Antifungals for Invasive Infections Delivered by Unconventional Methods; Aerosols, Irrigants, Directed Injections and Impregnated Cement

Abstract: The administration of approved antifungals via unapproved formulations or administration routes (such as aerosol, direct injection, irrigation, topical formulation and antifungal-impregnated orthopedic beads or cement) may be resorted to in an attempt to optimize drug exposure while minimizing toxicities and/or drug interactions associated with conventional (systemic) administrations. Existing data regarding such administrations are mostly restricted to uncontrolled case reports of patients with diseases refra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 183 publications
0
7
0
Order By: Relevance
“…The authors also indicated that the results might be influenced by the reduced number of studies included, the differences in patient age, the dosage, the course, and the frequency of drug administration [ 34 ]. Drew and Perfect emphasized that published data regarding the administration of antifungals by alternative routes are scarce and restricted to uncontrolled case reports or studies with small sample sizes [ 35 ]. Fitchenbaum et al reported that in a group of patients with HIV infection or CDC-defined AIDS, amphotericin B oral suspension had limited efficacy for treating fluconazole-refractory oral candidiasis.…”
Section: Discussionmentioning
confidence: 99%
“…The authors also indicated that the results might be influenced by the reduced number of studies included, the differences in patient age, the dosage, the course, and the frequency of drug administration [ 34 ]. Drew and Perfect emphasized that published data regarding the administration of antifungals by alternative routes are scarce and restricted to uncontrolled case reports or studies with small sample sizes [ 35 ]. Fitchenbaum et al reported that in a group of patients with HIV infection or CDC-defined AIDS, amphotericin B oral suspension had limited efficacy for treating fluconazole-refractory oral candidiasis.…”
Section: Discussionmentioning
confidence: 99%
“…They are simple to use and almost immediately absorbed by the skin. Tinea pedis on the soles of the feet is frequently treated using sprays [11].…”
Section: Conventional Antifungal Delivery Systemsmentioning
confidence: 99%
“…Powders are applied to body parts where moisture is a problem, like the space between the toes. Usually, they are used after washing and drying the impacted region [11].…”
Section: Conventional Antifungal Delivery Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…While favourable outcomes have been reported in the literature with usage of oral voriconazole for Aspergillus otomycosis [ 3 , 4 ], systemic antifungal treatment is often utilised only after topical therapy has failed, due to concerns of tolerability and side effects. Topical voriconazole has been utilised in case reports as an alternative option for treating refractory otomycosis failing to respond to usual therapeutic options [ 5 , 6 ]; though otic administration of topical voriconazole is not a conventional mode of drug delivery, and at present is not licensed for such use [ 7 ]. We report a case of intractable Aspergillus otomycosis with multiple relapses despite conventional topical and systemic antifungal treatment, and adjunctive usage of hyperbaric oxygen therapy.…”
Section: Introductionmentioning
confidence: 99%